Pengaruh Suasana Belajar Dan Keaktifan Siswa Terhadap Hasil Belajar Matematika Siswa - Arianti, Chindy Mei; Sulistyono, Bambang Agus; Samijo, Samijo (Peneliti.net, 2025)
This research aims to: (1) determine the influence of the learning atmosphere and student activity on mathematics learning outcomes; (2) determine the effect of student activity on student mathematics learning outcomes; and (3) determine the influence of the learning atmosphere and student activity on student mathematics learning outcomes. This research method uses ex post facto with a quantitative approach. The sample in this study was 51 students. Sampling used a cluster random sampling technique. Data collection uses documentation, questionnaires and tests methods. The data analysis techniques used in this research are descriptive statistics and inferential statistics. The data analysis requirements used in this research include a validity test and a reliability test. From the calculation results, the following results were obtained: (1) The influence of the learning atmosphere on mathematics learning outcomes obtained that the t-count results were greater than the t-table, namely (239,419 > 1,682). With the equation Y = 11.050 + 0.788; (2) The effect of student activity on students' mathematics learning outcomes obtained t-count results greater than t-table, namely (23,309 > 1,682). With the equation Y=78,095 + 1,000; (3) The influence of the learning atmosphere and student activity on mathematics learning outcomes. Students obtained f-count results greater than f-table, namely (831,286 > 3,238) with the equation Y = 150,953 + 2,632. The influence of the learning atmosphere and student activity on student mathematics learning outcomes was 97.7%.